(untitled) (Revista Brasileira de Contabilidade e Gestão, 2012)
This paper presents some concepts related to JavaServer Faces (JSF) frameworks Apache Tobago, PrimeFaces and RichFaces. The paper also presents a comparison between them by considering the following aspects: availability of components, documentation and support, frequency of updates and usage settings. Finally is presented which of the three analyzed frameworks is the best and most complete for application development with JSF.